EFEK BLENDING BAHAN BAKAR TERBARUKAN BUTANOL 5% PADA PERTAMAX TERHADAP PERFORMA MESIN BENSIN EFI 150 CC - Budi, Sigit Setijo; Sanjaya, Firman Lukman; Fatkhurrozak, Faqih; -, Syarifudin; Riyono, Agus Hut (Politeknik Harapan Bersama Tegal, 2024)
Butanol is an alternative energy that is being developed to overcome the energy crisis. This is because butanol has a high Octane number and oxygen content so it can optimize engine performance. This research was carried out to determine the impact of adding butanol to Pertamax on gasoline engine performance. The engine used is a 150 cc EFI petrol engine. The fuel uses Pertamax with butanol additive. Testing uses speed variations of 1000 – 3000 rpm. Test results: The performance of the 150 cc EFI petrol engine using the Pertamax-butanol mixture (P95B5) has increased compared to using pure Pertamax fuel (P100). This can be seen from the increase in torque and power with Pertamax-butanol fuel (P95B5) of 3.57 N.m and 1.12 kW, the highest increase at rpm 3000. Engine fuel consumption decreased when butanol was added compared to pure Pertamax (P100). The lowest fuel consumption occurred with Pertamax-butanol (P95B5) fuel at 0.21 ml/s when the engine speed was 100 rpm. Meanwhile, the highest fuel consumption occurred in Pertamax fuel (P100) at 0.62 ml/s when the engine speed was 3000 rpm